Simulating a Measurement of the 2nd Knee in the Cosmic Ray Spectrum with an Atmospheric Fluorescence Telescope Tower Array - Jiali Liu; Qunyu Yang; Yunxiang Bai; Zhen Cao (The Scientific World Journal)
A fluorescence telescope tower array has been designed to measure cosmic rays in the energy range of 1017–1018 eV. A full Monte Carlo simulation, including air shower production, light generation and propagation, detector response, electronics, and trigger system, has been developed for that purpose. Using such a simulation tool, the detector configuration, which includes one main tower array and two side-trigger arrays, 24 telescopes in total, has been optimized. The aperture and the event rate have been estimated. Furthermore, the performance of the Xmax⁡ technique in measuring composition has also been studied.